Religiousness and the Matchmaking of a Young Cleric with a Tomboy Woman Novel by Azzamine - Fadia Zahra Refani Putri; Suseno (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
In the development of modern literature, novels have various genres, each presenting different themes and values. One genre that has attracted much attention from readers is the religious novel. This type of novel not only presents fictional stories about human life buat also emphasizes religiosity, spirituality, and the relationship between humans and God Almighty.The purpose of his study is to examine the representation of the religiosity of the characters Azzam and Jasmine in Sophie Aulia’s novel Azzamine, particularly in the context of matchmaking prior to marriage. This study uses a qualitative descriptive method with primary data collection techniques. Primary data was obtained from the novel Azzamine, publishes in the February 2022, through reading and recording of quotations related of religiosity. Data analysis was conducted using Glock and Stark’s five dimensional theory of religiosity, namely the dimensions of belief, religious practice, knowledge, experience, and consequences. The results show that the characters Azzam and Jasmine Represent the five dimensions of religiosity identified by Glock and Stark. Jasmine’s belief and religious practices also changed after she was arranged to marry, or more precisely, after she married Azzam.